0770 Does Obesity Predict Severity of Obstructive Sleep Apnea in Children with Down Syndrome?. (27th April 2018) - Sanford, J; Super, E R; Pinter, J; Gordon, D; Pierce, M; Sage, K; Lam, D
Abstract: Introduction: Children with Down Syndrome are more likely to have OSA (30–60%), with increased severity and be obese or overweight. Etiology of OSA in children with DS is multifactorial: anatomy, low tone, and lymphoid hypertrophy. In typically developing children, obesity is a risk factor for more severe OSA; however, there are mixed findings in small studies that evaluate obesity and OSA severity in DS children. Our objective is to study the relationship between obesity and severity of OSA in DS patients. Methods: Retrospective cohort study of 508 pediatric Down syndrome patients who have been seen in the OHSU Down Syndrome Clinic seen between 11/2007 and 1/2015. The data is maintained in an IRB-approved Red Cap database. We reviewed demographic data including weight and height and polysomnogram data of these patients. Exclusion criteria included patients without PSG or weight/height data within 4 months of PSG. We measured outcomes based on initial PSG data (not subsequent studies). In the analysis, patients are stratified by age due to difference in plotting growth parameters in children <3 years old. We used CDC BMI percentile in children ≥3 years old and DS weight-for-length percentile in children <3 years old. Results: Based on preliminary analysis, in children ≥3 years old, AHI increases by 2.4% for every one unit increase in the BMI percentile (p=0.012, 95% CI = 0.784%, 4.2%). In children <3 years old, no significant relationship between weight-for-length percentile and AHI (p=0.739) in children <3 years old. Conclusion: BMI is one risk factor that can be modified, and weight management should be considered in children ≥3 years old. On the other hand, weight does not seem to be relevant to OSA severity in <3 years old, a group in which obesity poorly defined and other factors like neuromuscular tone may have greater significance. Support (If Any): OHSU Department of Pediatrics Biostats Pilot Award (Grant #0617ES), Private donations to the OHSU Foundation to support the Down Syndrome Program, OHSU Redcap, OHSU Biostatistics (Grant #UL1TR0002369).